2013
DOI: 10.1371/journal.pone.0076952
|View full text |Cite
|
Sign up to set email alerts
|

Urea Transporter UT-B Deletion Induces DNA Damage and Apoptosis in Mouse Bladder Urothelium

Abstract: BackgroundPrevious studies found that urea transporter UT-B is abundantly expressed in bladder urothelium. However, the dynamic role of UT-B in bladder urothelial cells remains unclear. The objective of this study is to evaluate the physiological roles of UT-B in bladder urothelium using UT-B knockout mouse model and T24 cell line.Methodology/Principal FindingsUrea and NO measurement, mRNA expression micro-array analysis, light and transmission electron microscopy, apoptosis assays, DNA damage and repair deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…This has led to the suggestion that urea enters umbrella cells across the apical membrane from the urine, via the endosomal pathway (1), and that UT-B then enables the exit of this urea out of the urothelium. The physiological relevance of this hypothesis is supported by the observation that there is a large increase in urea levels within the urothelium of UT-B knockout mice (4). An alternative hypothesis is that lack of UT-B in the kidneys will decrease urine concentrating ability (18,30) and hence increase urine volume.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This has led to the suggestion that urea enters umbrella cells across the apical membrane from the urine, via the endosomal pathway (1), and that UT-B then enables the exit of this urea out of the urothelium. The physiological relevance of this hypothesis is supported by the observation that there is a large increase in urea levels within the urothelium of UT-B knockout mice (4). An alternative hypothesis is that lack of UT-B in the kidneys will decrease urine concentrating ability (18,30) and hence increase urine volume.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, compared with many other tissues, very high UT-B RNA expression has been reported in the mouse bladder (30). Most recently, it has been reported that UT-B knockout mice suffered DNA damage and apoptosis in the bladder, strongly suggesting that UT-B plays a significant physiological role protecting the bladder urothelium (4). Since urea levels were significantly higher in the UT-B-null urothelium compared with wild-type urothelium, it has been suggested that UT-B specifically helps remove intracellular urea from the bladder urothelium (4).…”
mentioning
confidence: 99%
“…UT-A2 in liver and heart may facilitate efflux of metabolically generated urea, 49,51,52 and UTs in the inner ear have been postulated to facilitate urea transport between the endolymph and perilymph, contributing to fluid homeostasis. 48 Phenotype studies on UT-B knockout mice have revealed neuropsychiatric, 53 cardiac conduction, 54,55 bladder 56 and testicular 57 abnormalities, although the relevance of these phenotype findings is unclear, both because they lack plausible mechanisms, suggesting secondary effects, and because there are no studies of humans with loss-of-function mutations in UT-B that report extrarenal abnormalities.…”
Section: Ut Proteinsmentioning
confidence: 99%
“…Evidences have shown that an excess of intracellular urea accumulation damages cells and cell functions (DNA damage, abnormal cell phenotype transformation, genetic pathway activation, etc.) (11,(14)(15)(16). Since the bladder stores urine, its urothelium is inevitably and constantly exposed to a higher concentration of urea than any other tissues.…”
Section: Introductionmentioning
confidence: 99%